Synthesis and Modification of Nanostructured Thin Films - Mihailescu, Ion N. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue "Synthesis and Modification of Nanostructured Thin Films" highlights the recent progress in thin film synthesis/modification and characterization. New methods are reviewed for the synthesis and/or modification of thin films based on laser, magnetron, chemical, and other techniques. The obtained thin nanostructures are characterized by complex and complementary techniques. We think that most of proposed methods can be directly applied in production, but some others still need further elaboration for long-term prospective applications in lasers, optics, materials, electronics, informatics, telecommunications, biology, medicine, and probably many other domains. The Guest Editor and the MDPI staff are therefore pleased to offer this Special Issue to interested readers, including graduate and PhD students as well as postdoctoral researchers, but also to the entire community interested in the field of nanomaterials. We share the conviction that this can serve as a useful tool for updating the literature, but also to aid in the conception of new production and/or research programs. There is plenty of room for further dedicated R&D advances based on new instruments and materials under development.